2009
DOI: 10.1016/j.jim.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental flaws of immunoassays and potential solutions using tandem mass spectrometry

Abstract: Immunoassays have made it possible to measure dozens of individual proteins and other analytes in human samples for help in establishing the diagnosis and prognosis of disease. In too many cases the results of those measurements are misleading and can lead to unnecessary treatment or missed opportunities for therapeutic interventions. These cases stem from problems inherent to immunoassays performed with human samples, which include a lack of concordance across platforms, autoantibodies, anti-reagent antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
340
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(343 citation statements)
references
References 54 publications
2
340
0
1
Order By: Relevance
“…However, sCD163 levels did not correlate with the extent of skin sclerosis since sCD163 levels were similar between dSSc and lSSc patients. It has been reported that serum factors including heterophilic antibodies can bind to coating and detection antibodies in some ELISA systems using a pair of antibodies and cause the falsely elevated results [22][23][24]. Actually, we measured serum sCD163 using a sandwich ELISA in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…However, sCD163 levels did not correlate with the extent of skin sclerosis since sCD163 levels were similar between dSSc and lSSc patients. It has been reported that serum factors including heterophilic antibodies can bind to coating and detection antibodies in some ELISA systems using a pair of antibodies and cause the falsely elevated results [22][23][24]. Actually, we measured serum sCD163 using a sandwich ELISA in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…The peptide standard refers to the 13 separated by LC retention time as well. In contrast, autoantibodies and heterophilic anti-reagent antibodies are known to produce false positive and false negative results in sandwich immunoassays (33)(34)(35). These types of interferences are not observed in immuno-MRM-MS because the auto-and heterophilic antibodies are inactivated by reduction, alkylation, and enzymatic digestion during sample preparation for SISCAPA (36 -38).…”
Section: Discussionmentioning
confidence: 99%
“…The technique demonstrates impressive analytical specificity and is argued to be free of many of the limitations of IAs (e.g. matrix interference; Hoofnagle & Wener, 2009). Although the financial and logistical requirements of LC-MS/MS limit its widespread use, the technique is a sensitive reference measure, allowing for both the identification and quantification of compounds by combining the physical separation capacity of liquid chromatography with the mass analysis capability of mass spectrometry (Star-Weinstock et al, 2012;Turpeinen et al, 2012;Keevil, 2013).…”
Section: Assessing the Validity Of Eias With Liquid Chromatography Tamentioning
confidence: 99%